2014
DOI: 10.1042/bst20130273
|View full text |Cite
|
Sign up to set email alerts
|

Why don't plants have diabetes? Systems for scavenging reactive carbonyls in photosynthetic organisms

Abstract: In the present paper, we review the toxicity of sugar- and lipid-derived RCs (reactive carbonyls) and the RC-scavenging systems observed in photosynthetic organisms. Similar to heterotrophs, photosynthetic organisms are exposed to the danger of RCs produced in sugar metabolism during both respiration and photosynthesis. RCs such as methylglyoxal and acrolein have toxic effects on the photosynthetic activity of higher plants and cyanobacteria. These toxic effects are assumed to occur uniquely in photosynthetic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
18
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 32 publications
(21 citation statements)
references
References 36 publications
0
18
0
Order By: Relevance
“…Interestingly, the latter gene is physically located between a DNA repair gene (encoding RAD51) and a tRNA modification gene on scaffold 2777 in the A. digitifera draft assembly ( Figure 4—figure supplement 4 ). Glyoxalase I belongs to a system that carries out the detoxification of reactive carbonyls (RC), such as highly cytotoxic methylglyoxal, produced by sugar metabolism and the Calvin cycle ( Shimakawa et al, 2014 ). Methylglyoxal production in plastids increases with light intensity ( Takagi et al, 2014 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, the latter gene is physically located between a DNA repair gene (encoding RAD51) and a tRNA modification gene on scaffold 2777 in the A. digitifera draft assembly ( Figure 4—figure supplement 4 ). Glyoxalase I belongs to a system that carries out the detoxification of reactive carbonyls (RC), such as highly cytotoxic methylglyoxal, produced by sugar metabolism and the Calvin cycle ( Shimakawa et al, 2014 ). Methylglyoxal production in plastids increases with light intensity ( Takagi et al, 2014 ).…”
Section: Discussionmentioning
confidence: 99%
“…Methylglyoxal production in plastids increases with light intensity ( Takagi et al, 2014 ). Another gene encoding a putative RC scavenger ( Shimakawa et al, 2014 ) is short-chain dehydrogenase/reductase (SDR) that was derived in corals from an algal source ( Figure 4—figure supplement 5 ). Other alga-derived HGTs were from species containing plastids of red algal secondary endosymbiotic origin (i.e., chlorophyll c -containing lineages such as stramenopiles) ( Table 1 ).…”
Section: Discussionmentioning
confidence: 99%
“…Methylglyoxal is thus constantly produced in the plants during glycolysis reactions and in the Calvin cycle of photosynthesis (Figure 1) [11,20]. Under abiotic stress conditions such as salinity, drought, and cold stress, concentrations of MG in plant cells are reported to increase rapidly from 35–75 μM under normal conditions to 200 μM (2- to 6-fold) [21,22].…”
Section: Methylglyoxal Detoxification System In Plantsmentioning
confidence: 99%
“…Bechtold et al (28) in their pioneering work confirmed the presence of glycation products in exhaustive hydrolysates of plant leaf proteins. Continuing these studies, Shimakawa et al (29) proposed the endogenic sources of AGEs in plants and some corresponding anti-glycative mechanisms protecting the plants from deleterious effects of accumulated AGEs. Because of the high levels of carbohydrates, transition metals, and molecular oxygen in plant tissues, high levels of monosaccharide autoxidation (6) and therefore essential in vivo ␣-dicarbonyl and reactive oxygen species (ROS) production can be expected.…”
mentioning
confidence: 99%